IMPLEMENTASI MODEL CHILDREN LEARNING IN SCIENCE DALAM PEMBELAJARAN IPAS MATERI EKOSISTEM KELAS III - Putri, Dinda Ayu; Suntari, Yustia; Yudha, Chrisnaji Banindra (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
Understanding complex ecosystem material is often a challenge for elementary school students, so an effective learning model is needed. This study aims to test the effectiveness of the application of the Children Learning in Science (CLIS) model in science learning on ecosystem material for third grade elementary school students. The CLIS model that focuses on active learning through exploration, experimentation, and discussion is expected to improve students' understanding. The research method used is quantitative experiment with a nonequivalent control group design, involving an experimental group that applies the CLIS model and a control group that uses conventional methods. Data collection was carried out through pretests and posttests to measure student understanding, which were then analyzed for differences in order to see the increase in understanding between the two groups. The results showed that the experimental group experienced a significant increase in understanding of ecosystem material with an average increase in the posttest of 41.09%, while the control group only experienced an increase of 23.60%. Thus, it is concluded that the CLIS model is effective in improving the understanding of third grade elementary school students on ecosystem material compared to conventional methods. ABSTRAKPemahaman materi ekosistem yang kompleks sering menjadi tantangan bagi siswa sekolah dasar, sehingga diperlukan model pembelajaran yang efektif. Penelitian ini bertujuan untuk menguji efektivitas penerapan model Children Learning in Science (CLIS) dalam pembelajaran IPAS materi ekosistem pada siswa kelas III sekolah dasar. Model CLIS yang berfokus pada pembelajaran aktif melalui eksplorasi, eksperimen, dan diskusi diharapkan dapat meningkatkan pemahaman siswa. Metode penelitian yang digunakan adalah kuantitatif eksperimen dengan desain nonequivalent control group, melibatkan kelompok eksperimen yang menerapkan model CLIS dan kelompok kontrol yang menggunakan metode konvensional. Pengumpulan data dilakukan melalui pretest dan posttest untuk mengukur pemahaman siswa, yang kemudian dianalisis perbedaannya guna melihat peningkatan pemahaman antara kedua kelompok. Hasil penelitian menunjukkan bahwa kelompok eksperimen mengalami peningkatan pemahaman materi ekosistem yang signifikan dengan kenaikan rata-rata posttest sebesar 41,09%, sementara kelompok kontrol hanya mengalami kenaikan sebesar 23,60%. Dengan demikian, disimpulkan bahwa model CLIS efektif dalam meningkatkan pemahaman siswa kelas III sekolah dasar terhadap materi ekosistem dibandingkan dengan metode konvensional.